A study of prevalence of subclinical distal symmetrical sensorimotor polyneuropathy among diabetic patients - Singh, Sathvinder (2015)
Subclinical distal symmetrical sensorimotor polyneuropathy among diabetic patients is a common complication of diabetes that will lead to clinical neuropathy which causes increase morbidity and mortality and adds to the overall socio economic impact of diabetes mellitus globally. The objective of this study was to estimate the prevalence of subclinical distal symmetrical sensorimotor polyneuropathy among diabetic patients in our local population. Its other objectives was to determine any associated factors in its prevalence among diabetic patients. A total of 151 patients with no signs or symptoms of diabetic neuropathy were recruited in this study and had their vibration perception threshold(VPT) recorded using a biothesiometer at both their feet. A total of 79 patients had subclinical distal symmetrical sensorimotor polyneuropathy (52.3%) and 72 patients did not have neuropathy (47.7%). Age of patient (OR1.14, 95% CI:1.05, 1.24) and duration of diabetes (OR 1.42, 95% CI: 1.13, 1.79) were the factors associated with increase in prevalence of subclinical distal symmetrical sensorimotor polyneuropathy. It was also found that patients with other diabetic microvascular complications which were diabetic retinopathy (OR 14.75, 95% CI: 3.40, 63.91) and urine microalbuminuria (OR 72.63, 95% CI: 2.85,80.52) had increase frequency of subclinical neuropathy. As a conclusion, this study demonstrated a prevalence of 52.3% among diabetic patients between 18 to 75 years of age have subclinical distal symmetrical sensorimotor polyneuropathy. Its associated risk factors were age of patient and duration of diabetes. It also has a positive correlation with patient suffering from other microvascular complication mainly diabetic retinopathy and urine microalbuminuria. Based on this we need to be more vigilant in examining diabetic patients with such risk factors for neuropathy as early detection of neuropathy can prevent other worse outcomes such as diabetic foot ulcers as well as amputations.